Effect of low- and high-protein maternal diets during gestation on reproductive outcomes in the rat: a systematic review and meta-analysis. (19th December 2019) - Ajuogu, Peter K; Wolden, Mitchell; McFarlane, James R; Hart, Robert A; Carlson, Debra J; Van der Touw, Tom; Smart, Neil A
Abstract: Studies with animal models have consistently demonstrated adverse health outcomes in offspring born following nutritional manipulation during gestation. However, the effects of gestational dietary protein modification on reproductive outcomes at birth are less clear. We, therefore, conducted a systematic review and meta-analysis of controlled trials to determine whether high- or low-protein diets are associated with altered reproductive outcomes in a commonly studied species, the rat. Included studies were identified through a systematic search using electronic databases and manual literature review to identify randomized studies published between June 1972 and March 2019. Thirty-two studies were identified and used to analyze the effects of low- and high-protein gestational diets on litter size, litter weight, gestational weight gain, and gestational feed intake. The results indicate that low-protein diets significantly reduced litter weight ( P  < 0.00001) and gestational weight gain ( P  < 0.0006), but did not influence litter size ( P  = 0.62) or gestational feed intake ( P  = 0.25). In contrast, high-protein diets were found to reduce gestational feed intake ( P  = 0.004) but did not influence litter size ( P  = 0.56), litter weight ( P  = 0.22), or gestational weight gain ( P  = 0.35). The results suggest that low but not high-protein gestational diets alter reproductive outcomes at birth in rats.